PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT DALAM MENINGKATKAN LOYALITAS PELANGGAN PADA PENJUALAN TAS TOKO VANIASHOP BERBASIS WEB - heru saputro (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Kudus Regency is known as kretek city which is one of the regencies in Central Java province. Apart from being a city of clove, there are also religious tourism to culinary tourism as well as creative industries making bags that are sold in stores. Micro, small and medium enterprises (MSMEs) in Kudus have sprung up because of the potential that can bring benefits. Various kinds of information and technology are growing rapidly, especially for business activities, industry and others. Therefore, online marketing and direct communication are needed. Online marketing is used to support consumers and sellers in the process of buying and selling transactions, promotions, customer loyalty, and communication so that it can be established in realtime and not limited by time and distance, by utilizing an internet connection. With online marketing, customers do not have to come to the store and make payments on the spot, so it requires a process that requires a lot of time. The research objective is to build an online marketing system with Customer Relationship Management. The model used for the development of online marketing is a waterfall model whose scope starts from analysis to maintenance. So with online marketing with Customer Relationship Management, consumers are expected to easily use it.